NiO and CrOx interaction promoting in situ generation of the coordinatively unsaturated Cr–O acid–base for oxygen-lean propane dehydrogenation. Issue 2 (12th December 2022) - Ren, Yu; Chu, Xiao; Cao, Qi; Xie, Zean; Kong, Lian; Fan, Xiaoqiang; Xiao, Xia; Zhao, Zhen
Abstract : The interaction between NiO and CrO x species increases the reducibility of Cr–O–Ni lattice oxygen, which is consumed to form an oxygen vacancy and a nearby unsaturated Cr–O acid–base pair as the possible active sites for PDH reaction. Abstract : Highly dispersed Ni and Cr-doped MgAl x O y composite oxides ( x Ni20Cr–O) were prepared by calcining as-prepared MgAl hydrotalcite with cationic plate lattice-confined Ni and Cr. The x Ni20Cr–O catalysts were used as the catalysts for O2 -lean propane dehydrogenation (PDH), and the 10Ni20Cr–O catalyst exhibited 90% C3 H6 selectivity at 34% C3 H8 conversion after two induction periods. Operando Raman, ultraviolet-visible diffuse reflectance, X-ray photoelectron spectroscopy, etc. were conducted to investigate the valence evolution of Ni and Cr species under O2 -lean PDH conditions. The surface Cr 6+ species were reduced in the first induction period. In the second induction period, a mutation reduction phenomenon (the abrupt generation of CO and CO2 ) happened because of the interaction between NiO and CrO x species to increase lattice oxygen reducibility, such as the lattice oxygen of Cr–O–Ni. These promote lattice oxygen consumption and oxygen vacancy formation. Results of density functional theory (DFT) calculations indicate that the coordinatively unsaturated Cr–O acid–base pairs close to oxygen vacancy as possible active sites exhibit higher PDH performance than stoichiometric Cr 3+ –O bonds. The small amount of molecular oxygen in the reactant gas not only inhibits the reduction of NiO species into metal Ni for hydrogenolysis, but can also in situ oxidize the over-reduced 10Ni20Cr–O catalyst, which exhibits excellent stability without deactivation within 20 h.